Stadiums in the small screen : discussing the threat of new media advents on sport consumption in Singapore - M Kumar, Magashastini (2016)
The advent of New Media from the 1980s had many ramifications on the consumer market within the sport realm. Sport consumption started shifting from a participant-centric one to that of a spectator-centered one. In Singapore, the sport of soccer offers a very important case study in identifying New Media as a factor in the falling attendance rates at soccer games in Singapore. Mediums of New Media has also introduced higher quality games in the form of the European leagues which have drawn much interest away from local soccer. Literature have proven that there is indeed a shift from direct to indirect sport consumption. While New Media threatens the direct consumption of soccer in Singapore, it can also be harnessed as an important tool in the promotion of soccer consumption in Singapore.